Review and comparison of empirical thermospheric mass density models. (November 2018) - He, Changyong; Yang, Yang; Carter, Brett; Kerr, Emma; Wu, Suqin; Deleflie, Florent; Cai, Han; Zhang, Kefei; Sagnières, Luc; Norman, Robert
Abstract: Atmospheric drag, as one of the largest non-gravitational perturbations in low Earth orbit (LEO), can dramatically decay the orbit of LEO satellites with both secular and periodic effects. Hence, it plays a critical role in orbit prediction related products, and research on orbit determination, orbital uncertainty propagation and collision avoidance. Although many empirical thermospheric mass density (TMD) models have been proposed in the past few decades, precise determination of atmospheric drag is still a challenging task. In order to give a comprehensive review of the current empirical TMD models, focusing on their impact on orbital dynamics, this review summarises and investigates the most representative classes of models, including the Jacchia, Mass Spectrometer Incoherent Scatter (MSIS), Jacchia-Bowman (JB), and Drag Temperature Model (DTM). Twelve representative models are selected for further comparison in terms of spatial variations and assessing their ability to capture complex features, e.g., equatorial mass density anomaly (EMA). Further validation is done with accelerometer-derived TMD from LEO satellites. The results show that only DTM2013 can capture the EMA feature and the drag coefficient calculated by physical models used in the TMD estimation may be underestimated. The performance of these models in orbit prediction is comprehensively evaluated under different solar and geomagnetic conditions. JB2008 and DTM2013 outperform the other selected models during low and high solar activity. Standard deviation is found to be less affected by the bias in the accelerometer- and model-derived TMD, than mean value and root-mean-square error. The coupling effect between the TMD and ballistic coefficient, and the potential directions for future efforts in TMD modelling are also discussed.